Pemikiran Politik (Madilog) Tan Malaka Menuju Kemerdekaan Indonesia - Islam, Muhammad Fajrul (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2016)
This research aims to explore what became Tan Malaka's political thought towards Indonesian independence. The theory (approach) used as an analytical tool in this research is the theory of thought, the concept of ideology, socialism and is the theory of thought, the concept of ideology, socialism and Marxism. marxism. While the method used in this research is a qualitative descriptive method, namely research intended to be able to provide a systematic description of the phenomena Based on the results of this study, Tan Malaka's thoughts towards Indonesian independence can be divided into three parts. towards Indonesian independence can be divided into three parts. First, the basic concept of Tan Malaka's thought which was influenced by Hegel's Dialectic and Materialism. Hegel's Dialectic and Marx-Engels' Dialectical Materialism, Madilog, and Tan Malaka's Struggle for Indonesian Independence. and Tan Malaka's Struggle for Indonesian Independence. Second, the philosophy of the state according to Tan Malaka with the concept of historical withdrawal from the from the time of early humans to the formation of Indonesia. Third, socialist economic design and the independent state